THE ROLE OF LEADERSHIP STYLE IN EMPLOYEE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Ka Utama, Hendri; Fuadah, Luk Luk (LP2M IBK Nitro, 2025)
Amid the dynamics of global business competition, leadership capabilities play a vital role in optimizing HR productivity while ensuring organizational sustainability. The latest data from the World Economic Forum (2023) reveals that more than half of world-class companies place leadership as a key component of strategic success. However, there is still debate about which leadership style is most effective in driving employee performance. This study is designed to explore the impact of several leadership styles—such as transformational, transactional, and authentic—on employee productivity, while examining how performance management systems function as a mediating factor. The research method used is a systematic literature review by analyzing previous studies indexed in Scopus and Google Scholar. The results of the study show that transformational leadership significantly strengthens employee motivation, commitment, and innovation, while Although transactional leadership is often considered rigid, this approach has proven to be efficient in work environments that prioritize discipline and structure, such as the manufacturing sector or emergency services. In addition, an effective performance management system can strengthen the relationship between leadership style and employee performance. These findings provide practical implications for organizations in designing more effective leadership training programs and performance management systems.